Review Paper on Attack Type and Intrusion Detection System in Cloud Computing - Soni, Manoj Kumar; Singh, Megha (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
In any information system intrusions are the activities that damage the security and integrity of the system. Over the past few decades the network based system has grown at an explosive rate with innovations in communication and information technologies. While the computer network and their related applications brought the world together by bridging the information gap among people, it has also made it easier to leads unauthorized activity not only from external attackers but also from internal attackers, such as disgruntled employees and people abusing their privileges for personal gain. In this review paper we will try to traverse Cloud, Characteristics of Cloud, Application of Cloud, and Security issues related to Cloud. There is technique IDS which is used to detect Intrusion, we have to study this system with cloud computing concern. IDS should be used on Cloud model in a very effective way to sort out some security related challenges.